Effects of prevalence and feedback in the identification of blast cells in peripheral blood: expert and novice observers - Wanyi Lyu; Jennifer S. Trueblood; Jeremy M. Wolfe (Cognitive Research)
Abstract Low target prevalence affects perceptual decisions on both simple and complex stimuli. Without prior knowledge of how often targets may appear, trial-by-trial accuracy feedback modulates the effects of low prevalence partially by providing observers with information about the target base rate. Using simple colored dots, Lyu (PBR 28:1906–1914, 2021) found that at low prevalence, observers demonstrate a classical low prevalence effect (LPE) when receiving feedback. This involves a conservative shift of the decision criterion where observers are less likely to call an ambiguous item a target. In the absence of feedback, observers adopted more liberal criteria and became more likely to classify an item as a target, producing a Prevalence-Induced Concept Change (PICC, Levari et al., Science 360:1465–1467, 2018). The present study examines whether the effects of low prevalence and feedback are modulated by expertise. Novice (n = 26) and expert (n = 24) observers performed a cancer cell discrimination task. The prevalence of cancerous “blast cells” and the presence or absence of trial-by-trial accuracy feedback were manipulated. Unsurprisingly, medical professionals performed better than trained novices. Importantly, both experts and novices showed an LPE with feedback, although that LPE was weaker in experts, suggesting expertise may modulate the size of the LPE. Low prevalence had little effect on the criterion in the absence of feedback in this setting. For both novices and experts, initial exposure to trials with feedback influenced criteria in subsequent no feedback conditions. Interestingly, experts showed a conservative criterion at the start of the experiment, even without having experienced a feedback block. This could reflect previous training or working in a low prevalence setting. Our study shows the interactions of the effects of low prevalence, feedback, and expertise on perceptual decisions and provides direct evidence for prevalence and feedback effects on expert decisions.